The Relationship Among Information and Communication Technology Utilization, Self-Regulated Learning and Academic Performance of Prospective Teachers - Onivehu Adams, Ogirima; Adegunju Kabir, Adewale; Ohawuiro Onyinyechi, Emilia; Oyeniran Bunmi, Juliana (Acta Didactica Napocensia, 2018)
This study investigated the relationship among Information Communication Technology utilization, self-regulated learning and academic performance of prospective teachers. The ex-post facto design (correlation method) was employed for the study. The research subjects were 580 prospective teachers who were drawn using multi-stage sampling technique from University of Ilorin, Nigeria. Seven research questions were generated while four hypotheses were tested at 0.05 level of significance. A researcher-constructed questionnaire tagged "Information Communication Technology Utilization and Self-Regulated Learning Questionnaire (ICTUSRLQ)" was used for data collection. The instrument was administered on 60 selected prospective teachers outside the sample location through test-retest method; it yielded a reliability coefficient of 0.79 that was obtained through the Cronbach's Alpha formula. Data were analysed with percentage, mean and rank order, /-test, Pearson Product Moment Correlation and multiple regression statistical tools. The findings revealed that prospective teachers have a high level of ICT utilization, self-regulation and academic performance; gender did not influence prospective teachers' ICT utilization, self-regulation and academic performance; there was a significant relationship between Information Communication Technology utilization and self-regulated learning and that there was a significant composite relationship among ICT utilization, self-regulation (elaboration, organization, critical thinking, metacognition, peer learning and help seeking) and academic performance of prospective teachers. The researchers recommended that self-regulation training and ICT competence capacity building workshops should be organized for prospective teachers in University of Ilorin.